1997
DOI: 10.1002/j.1550-8528.1997.tb00580.x
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Response to Mercaptoacetate in Osborne‐Mendel and S5B/PL Rats

Abstract: SINGER, LORI K, DAVID A YORK, GEORGE A BRAY. Feeding response to mercaptoacetate in Osborne-Mendel and S5B/PL Rats. Obes. Res. 1997;5:587-594. The purpose of this experiment was to determine if Osborne-Mendel (OM) rats, which are susceptible to dietary-induced obesity, and SSB/PL (S5B) rats, which are resistant to dietary-induced obesity, differ in their feeding responses to mercaptoacetate (MA), which blocks fatty acid oxidation, or 2-deoxy-~-glucose (2DG), which blocks glucose utilization. 2DG (100 mgkg or 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In addition, numerous differences in feeding behavior have been reported. The stimulation of food intake by ␤-mercaptoacetate, an inhibitor of fatty acid oxidation, is reduced in S5B/Pl rats compared with the response in OM rats, whereas the increase in food intake in response to 2-deoxy-D-glucose, an inhibitor of glucose use, is similar in both strains (6). Other data also suggest a difference in the response to fatty acids in the two strains.…”
Section: Introductionmentioning
confidence: 93%
“…In addition, numerous differences in feeding behavior have been reported. The stimulation of food intake by ␤-mercaptoacetate, an inhibitor of fatty acid oxidation, is reduced in S5B/Pl rats compared with the response in OM rats, whereas the increase in food intake in response to 2-deoxy-D-glucose, an inhibitor of glucose use, is similar in both strains (6). Other data also suggest a difference in the response to fatty acids in the two strains.…”
Section: Introductionmentioning
confidence: 93%
“…Studies in animals indicate that this increased food intake is predominately carbohydrate and/or protein but not fat, even when fat is the only available nutrient (Singer et al 1997). The peripheral effects of 2-mercaptoacetate are blocked by hepatic vagotomy, but the effects of methyl palmoxirate are not (Ritter & Taylor, 1989, 1990.…”
Section: Ketones Fatty Acids and Lipoproteinsmentioning
confidence: 99%
“…The OM rat is more insulin‐resistant compared to the S5B/P1 rat (5) and has an attenuated activity of the fatty acid‐sensitive K + channel in their taste buds (6). In addition, numerous differences in their response to feeding modulators have been reported (4,7,8,9). These have suggested that the hypothalamic areas are involved in the sensitivity of OM rats for the HF diet‐induced obesity (10).…”
Section: Introductionmentioning
confidence: 99%